AN AN ANALYSIS STUDENT’S ABILITY IN WRITING PROCEDURE TEXT BY USING PICTURE SERIES AT SMP TELADAN MEDAN - ELTP LTP; Sri Ninta Tarigan; Lisnawaty br Ginting (English Language Teaching Prima Journal (ELT), 2020)
Abstract This research purposed to know the students‟ ability in writing procedure text . The location of this research was in SMP Teladan Medan.The time that was spend in this research was two days. This research was applied by qualitative content analysis. The subject of the research was the students at grade EIGHTH GRADE OF SMP TELADAN MEDAN . Students consist of 26 students. The instruments that used in this research was a test of writing procedure text, interview. The test was asking the students to write the procedure text by using picture series well. Based on the result of the research, the students‟ ability in writing procedure text was low. From this research, there are two instruments in examining their ability including vocabulary,style,mechanism,grammar. It is hoped that by the finding of these trouble, there will be future research on this subject so that there will be some method or strategy that enable to overcome these troubles. engl Key words: ability, writing, procedure text, picture series